PELATIHAN PENGGUNAAN APLIKASI CANVA PADA GURU SDN 1 BANJAREJO MALANG SEBAGAI UPAYA MENCIPTAKAN MEDIA PEMBELAJARAN YANG KREATIF - Alfin Dwi Cahyani; Arif Kiyat Bhaktiyana; Didi Suhendra; Krisantus Pius Usifa; Alfin Dwi Cahyani; Arif Kiyat Bhaktiyana; Didi Suhendra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: Students will more easily remember and understand the lessons delivered by theteacher when they use interesting learning media such as broadcasts or displaysproduced from learning media. Canva is a graphic design tool that facilitates thecreation of various artistic content online. Canva training materials as an innovationin creating creative learning media were chosen by researchers as a step to realizingquality education that is in line with this technological era. So the aim of this trainingis as an effort to create creative and innovative learning media with the help of theCanva application for teachers at SDN 1 Banjarejo Malang. The method used isthrough lectures, simulations and demonstrations in the form of counseling andtraining. The training was carried out by providing material to all participants as wellas demonstrations regarding the creation of teaching modules, Power Points,animated videos, brochures, PPDB pamphlets and so on. Based on the results of theCanva training that has been carried out, it can be concluded that the trainingregarding the use of the Canva application has had a significant impact on theunderstanding and creativity of teachers